Identifikacija priporočil, razvoj in testiranje uporabe piktogramov za izboljšanje komunikacije starejših v socialnovarstvenih zavodih - Krantić, Nadis (Obzornik zdravstvene nege, 2018)
Introduction: Pictograms are an image-based communication tool that improves communication between providers of health and social services and the elderly. The study had three research goals: (i) to identify recommendations for creating pictograms suitable for elderly users of social care institutions; (ii) develop pictograms based on identified recommendations; and (iii) to evaluate their usefulness.Methods: The study was based on a mixed method approach and consisted of three parts: (i) an analysis of scientific literature and conducting interviews with 4 nurses working in social care institutions to identify the recommendations for pictograms development, (ii) creating a pictogram, (iii) quasi-experiment with the goal to evaluate the usefulness of pictograms. We used univariate statistics (frequency and relative frequency) for data analysis.Results: Identified recommendations for pictograms relate to the general design of pictograms, the use of colors and shapes, and the location of pictograms. Interviews with four nurses further clarified the recommended location of pictograms and the content of pictograms that should represent: "risk of burns", "hand hygiene", "danger of falling", "risk of impact with the door", "dining room", and "occupational therapy". Evaluation of the developed pictograms with 30 social care institution users showed an adequate understanding of pictograms and their usefulness.Discussion and conclusion: Identified recommendations are a good basis for further design of pictograms for users of social care institutions. A more extensive use of pictograms in social care institutions would help to ensure better communication with the elderly and assist in ensuring safety and adequate orientation of the elderly.
Keywords: communication; image-based communication; institucionalno varstvo; institutional care; komunikacija; razvoj orodij; slikovna komunikacijska orodja; tool development